Barriers and Enablers to Organ Donation After Circulatory Determination of Death: A Qualitative Study Exploring the Beliefs of Frontline Intensive Care Unit Professionals and Organ Donor Coordinators. Issue 7 (July 2018) - Squires, Janet E.; Graham, Nicole; Coughlin, Mary; Chassé, Michaël; Linklater, Stefanie; Greenough, Megan; Grimshaw, Jeremy M.; Shemie, Sam D.; Dhanani, Sonny; Knoll, Gregory A.
Abstract : Background: A shortage of transplantable organs is a global problem. The purpose of this study was to explore frontline intensive care unit professionals' and organ donor coordinators' perceptions and beliefs around the process of, and the barriers and enablers to, donation after circulatory determination death (DCDD). Methods: This qualitative descriptive study used a semistructured interview guide informed by the Theoretical Domains Framework to interview 55 key informants (physicians, nurses, and organ donation coordinators) in intensive care units (hospitals) and organ donation organizations across Canada. Results: Interviews were analyzed using a 6-step systematic approach: coding, generation of specific beliefs, identification of themes, aggregation of themes into categories, assignment of barrier or enabler and analysis for shared and unique discipline barriers and enablers. Seven broad categories encompassing 29 themes of barriers (n = 21) and enablers (n = 4) to DCDD use were identified; n = 4 (14%) themes were conflicting, acting as barriers and enablers. Most themes (n = 26) were shared across the 3 key informant groups while n = 3 themes were unique to physicians. The top 3 shared barriers were: (1) DCDD education is needed for healthcare professionals, (2) a standardized and systematic screening process to identify potential DCDD donors is needed, and (3) practice variation across regions with respect to communication about DCDD with families. A limited number of differences were found by region. Conclusions: Multiple barriers and enablers to DCDD use were identified. These beliefs identify potential individual, team, organization, and system targets for behavior change interventions to increase DCDD rates which, in turn, should lead to more transplantation, reducing patient morbidity and mortality at a population level.